An RNA thermometer dictates production of a secreted bacterial toxin. - Christian Twittenhoff; Ann Kathrin Heroven; Sabrina Mühlen; Petra Dersch; Franz Narberhaus (PLoS Pathogens)
Frequent transitions of bacterial pathogens between their warm-blooded host and external reservoirs are accompanied by abrupt temperature shifts. A temperature of 37°C serves as reliable signal for ingestion by a mammalian host, which induces a major reprogramming of bacterial gene expression and metabolism. Enteric Yersiniae are Gram-negative pathogens accountable for self-limiting gastrointestinal infections. Among the temperature-regulated virulence genes of Yersinia pseudotuberculosis is cnfY coding for the cytotoxic necrotizing factor (CNFY), a multifunctional secreted toxin that modulates the host's innate immune system and contributes to the decision between acute infection and persistence. We report that the major determinant of temperature-regulated cnfY expression is a thermo-labile RNA structure in the 5'-untranslated region (5'-UTR). Various translational gene fusions demonstrated that this region faithfully regulates translation initiation regardless of the transcription start site, promoter or reporter strain. RNA structure probing revealed a labile stem-loop structure, in which the ribosome binding site is partially occluded at 25°C but liberated at 37°C. Consistent with translational control in bacteria, toeprinting (primer extension inhibition) experiments in vitro showed increased ribosome binding at elevated temperature. Point mutations locking the 5'-UTR in its 25°C structure impaired opening of the stem loop, ribosome access and translation initiation at 37°C. To assess the in vivo relevance of temperature control, we used a mouse infection model. Y. pseudotuberculosis strains carrying stabilized RNA thermometer variants upstream of cnfY were avirulent and attenuated in their ability to disseminate into mesenteric lymph nodes and spleen. We conclude with a model, in which the RNA thermometer acts as translational roadblock in a two-layered regulatory cascade that tightly controls provision of the CNFY toxin during acute infection. Similar RNA structures upstream of various cnfY homologs suggest that RNA thermosensors dictate the production of secreted toxins in a wide range of pathogens.